Quality engineering for Network Security Products: Lessons and Best Practices - Neha Kulkarni (North American Journal of Engineering Research, 2023)
In today’s transforming network security environment, the quality of security products that are offered as solutions is critical in offering protection against constantly emerging threats. The purpose of this research paper is to review and evaluate the concepts of quality engineering customized to network security products and to identify the emerging and recognized patterns and trends of this field based on the experiences from the practice. Based on the case analysis, reports, and experts’ opinions, the study reveals the factors that define network security solutions’ efficacy and dependability. The paper then outlines the strategies of quality engineering like threat modeling, conducting vulnerability tests, and integrating security testing with the development processes. It is focused on the identification of security issues and timely mitigation, with help of automated testing, constant monitoring and following the best practices and regulations. This paper’s results suggest that using a proactive quality engineering approach—implementing security from the ground up and adapting it dynamically to threats as and when they appear—improves overall network security product reliability and ruggedness. The study also defines typical difficulties, for instance, handling of intricate security necessities and the presence of appropriate mechanisms for tackling threats, and gives strategies for surmounting these hurdles. The practices described in detail in the paper include the use of automatic security testing tools, regular update and patching, and security consciousness among the development teams. Thus, by adhering to such practices in their work, organizations can enhance the availability and efficiency of network security products, which will lead to enhancing the level of protection in the digital space. This research is beneficial for quality engineers, developers, and security specialists to improve the quality and security of the network protection solutions in such a rapidly changing environment.